1, 000 Years of House Change at Cape Espenberg, Alaska: A Case Study in Horizontal Stratigraphy. Issue 3 (20th July 2013) - Darwent, John; Mason, Owen K.; Hoffecker, John F.; Darwent, Christyann M.
Abstract: Cape Espenberg is on the farthest southwestern extent of Kotzebue Sound, Alaska, just above the Arctic Circle, and is a peninsula composed of a series of dune-covered beach ridges. As part of a larger research initiative, extensive mapping to record all cultural features and characterize the topography of approximately 1 km 2 on the southeastern terminus of the cape was undertaken in 2007 and 2010. The primary purpose of this mapping was to explore the use of the cape for the past 1, 200 years using one of the unique aspects of beach-ridge archaeology: horizontal stratigraphy. There were 11 intervals of beach ridge/dune development, and with the exception of one truncated ridge and the modern ridge, Thule-Iñupiaq people built semi-subterranean winter houses on each ridge. A total of 117 house depressions along with related cache pits, artifact scatters, whale bone, and hearths were identified; distribution of house forms indicate that Cape Espenberg has had an unbroken stream of cultural continuity. However, in terms of house architecture and community patterning, it appears that there has been a reduction of certain architectural components over time. Houses also occur more frequently in isolated contexts. Both aspects are coincident with the onset of the Little Ice Age.